Arbovirus exposure and subclinical myocardial dysfunction in an Indigenous population in Northeast Brazil: a cross-sectional study - Jandir Mendonça Nicacio; Carlos Dornels Freire de Souza; Ricardo Khouri; Vanessa Cardoso Pereira; Rodrigo Feliciano do Carmo; Pedro Vinícius Amorim de Medeiros Patriota; Sávio Luiz Pereira Nunes; Jeová Cordeiro de Morais Júnior; Manoel Barral-Netto; João Augusto Costa Lima; Anderson da Costa Armstrong (BMC Infectious Diseases)
Abstract Background Human activities, such as urbanization and climate change, have facilitated the spread of arbovirus-carrying vectors, disproportionately affecting vulnerable traditional Indigenous communities. Objective To explore the relationships between subclinical myocardial dysfunction, assessed by global longitudinal strain (GLS), and comprehensive arbovirus serology in an Indigenous population, while also describing the serological and epidemiological profile of dengue, chikungunya, and Zika viruses. Methods This ancillary study is part of the first phase (2016–2017) of the Project of Atherosclerosis among Indigenous Populations (PAI), a cross-sectional study involving participants from two Indigenous communities with different degrees of urbanization and a highly urbanized city in Northeast Brazil. We assessed the seroprevalence of dengue, chikungunya, and Zika viruses in the Fulni-ô Indigenous community, the less urbanized and most traditional group. Additionally, we explored the relationship between these viruses and subclinical heart disease, assessed by speckle-tracking echocardiography-derived GLS. Results One hundred seventy-four participants were included, with a median age of 45.0 years (interquartile range 38.0–55.0). The majority were female (58.6%; n = 102). The prevalence of anti-ZIKV IgG was 95.3%; anti-DENV IgG was 85.8%, and anti-CHIKV IgG was 70.9%. GLS abnormalities were detected in nearly half (48.3%) of the cohort. However, no significant association was found between arbovirus serology and GLS. Conclusions The findings reveal a high prevalence of positive serology for arboviruses and a significant rate of subclinical cardiac dysfunction. There was no significant association between reduced left ventricular longitudinal strain and positive arbovirus serology, likely due to the limited number of participants with indications of acute contact with the viruses studied. However, the unprecedented and relevant results of this study are noteworthy, as they address critical public health issues, particularly in vulnerable populations. Further research is needed to explore these findings in more depth.